Rooting language in Arabic dialect Alkhozstanah - عاطي عبيات (College of Education for Women, 2019)
This study Arabic dialect prevailing in the province of Khuzestan [southwest Islamic Republic of Iran] as one of the Arabic dialects abundant qualities and characteristics of linguistic entrenched in the foot, which includes among Tithe thousands composed of vocabulary and structures and phrases classical that live up to the pre-Islamic era, if what Tasha researcher and reflect accurately the find of a large number of phrases and vocabulary and acoustic properties by nature accent, and formal, and nature of the synthetic, and characteristics semantic and contextual in this dialect studied without being something of them heavy on the tongue and without displays her tune or Tasha or distortion and so on all of which constitute a catalyst in that linger researcher and delve deeper into exposing that works to lift all that is precious and useful out of it to provide service to classical Arabic and correct everything that can be corrected and a throwback to his roots and remove dust vernacular him. This study aimed at rooting linguistic dialect studied and view their assets in terms of use of the classical Arabic and other dialects (languages) ancient